Millennium development goals, agricultural growth and openness - Imai, K; Gaiha, R (University of Oxford, 2003)
Millennium development goal (MDG) of poverty reduction aims for halving of the head-count ratio over the period 1990-2015. Available studies draw attention to the gap between observed and required growth rates, the difficulties of sustaining the latter over time, and whether the policy stance of a government makes a difference to its overall performance. Trade-offs between growth and redistribution in achieving the MDG have also been examined. The present study builds on earlier work in several respects. A two-stage procedure is developed in which income per capita depends on agricultural GDP, a measure of openness of the economy, and regional characteristics in the first stage, and poverty depends on the (estimated) income per capita, a measure of income inequality, and regional characteristics in the second stage. Alternative estimation techniques - including a panel data method- have been employed to check the robustness of the results. The feasibility of halving poverty is examined at the global, regional and country levels. The gaps between required and observed growth rates of aggregate and agricultural income, and the trade-offs between growth and redistribution of income are assessed. While doubts persist about the feasibility of halving poverty in some regions, the results bring into sharper relief the potential of redistribution in achieving this goal.